Analysis of the trimetazidine market in Ukraine and Poland for the treatment of cardiovascular diseases - Zlagoda, Viktoriya; Bobrytska, Larisa (Annals of Mechnikov's Institute, 2023)
Today in the world, cardiovascular diseases are the most common cause of death in the world, among which coronary heart disease is the main cause of mortality from cardiovascular diseases. The purpose of the study is the analysis of medicines registered in Ukraine and Poland with INN trimetazidine for the treatment of CVD. Research materials and methods. The data of the State Register of Medicinal Products of Ukraine for 2022, declared wholesale and retail prices for medicinal products in Ukraine as of August 2022, and retail prices of online pharmacies in Poland became the material of the study. Research methods: frequency and content analysis. Results and discussion. As a result of the content analysis, it was established that 14 trade names (TN) are registered on the pharmaceutical market of Ukraine, but only 5 TNs are represented on the market, which are presented in the form of tablets with the advantage of domestic production, in contrast, 10 TNs are represented on the Polish market also only in in the form of tablets. As a result of ATS/DDD-methodology, it was established that the cost of an average daily dose of trimetazidine in Ukraine ranged from UAH 1.86. up to UAH 6.87, in Poland - from UAH 1.72. up to UAH 7.16 in terms of prices of trimetazidine drugs. Conclusions. As a result of the content analysis, an assortment of medicinal forms of TN trimetazidine registered on the territory of Ukraine and consisting of 14 trade names was established, where 5 TN are presented in the form of tablets on the pharmaceutical market of Ukraine, of which 80% are produced by national manufacturers. 10 TN are presented on the pharmaceutical market of Poland and only in the form of tablets. The cost of Trimetazidine drugs in Ukraine was determined, where the cost of 1 package ranged from UAH 29.4 to UAH 164.03. and in Poland from UAH 90.40. up to UAH 471.17